HIV Testing Experience and Risk Behavior Among Sexually Active Black Young Adults: A CBPR‐Based Study Using Respondent‐Driven Sampling in Durham, North Carolina. Issue 3 (17th April 2015) - MacQueen, Kathleen M.; Chen, Mario; Jolly, David; Mueller, Monique P.; Okumu, Eunice; Eley, Natalie T.; Laws, Michelle; Isler, Malika Roman; Kalloo, Allison; Rogers, Randy C.
Abstract: African Americans are disproportionately affected by the HIV epidemic inclusive of men who have sex with men, heterosexual men, and women. As part of a community‐based participatory research study we assessed HIV testing experience among sexually active 18–30 year old Black men and women in Durham, NC. Of 508 participants, 173 (74 %) men and 236 (86 %; p = 0.0008) women reported ever being tested. Barriers to testing (e.g., perceived risk and stigma) were the same for men and women, but men fell behind mainly because a primary facilitator of testing—routine screening in clinical settings—was more effective at reaching women. Structural and behavioral risk factors associated with HIV infection were prevalent but did not predict HIV testing experience. Reduced access to health care services for low income Black young adults may exacerbate HIV testing barriers that already exist for men and undermine previous success rates in reaching women.